Mode-selective phonon excitation in gallium nitride using mid-infrared free-electron laser. (13th January 2017) - Kagaya, Muneyuki; Yoshida, Kyohei; Zen, Heishun; Hachiya, Kan; Sagawa, Takashi; Ohgaki, Hideaki
Abstract: The single-phonon mode was selectively excited in a solid-state sample. A mid-infrared free-electron laser, which was tuned to the target phonon mode, was irradiated onto a crystal cooled to a cryogenic temperature, where modes other than the intended excitation were suppressed. An A 1 (LO) vibrational mode excitation on GaN(0001) face was demonstrated. Anti-Stokes Raman scattering was used to observe the excited vibrational mode, and the appearance and disappearance of the scattering band at the target wavenumber were confirmed to correspond to on and off switching of the pump free-electron laser and were fixed to the sample vibrational mode. The sum-frequency generation signals of the pump and probe lasers overlapped the Raman signals and followed the wavenumber shift of the pump laser.